Polyurethane resin-based water-lubricated bearing composite material and preparation method thereof
By using polyurethane resin-based composite materials in water-lubricated bearings, combining the synergistic effect of nanofunctional fillers and solid lubricants, the problem of excessive material wear in the boundary lubricating state of water-lubricated bearings is solved, and the wear resistance of the material is significantly improved. Service life.
Patent Information
- Application Number
- CN202411567179.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the boundary lubricated bearings, in the boundary lubricated state or under dry sliding conditions, contact between friction pairs is inevitable, resulting in excessive wear of the material and affecting the reliability and service life of the moving system.
Polyurethane resin-based water-lubricated bearing composite material is made of nanofunctional fillers (such as concave and concave rock powder), solid lubricants, polyurethane matrix and polyurethane curing agent, and prepared by drying, stirring and mixing, demolding and vulcanizing. .
Under water lubrication conditions, the synergy between the concave and concave rock stone and solid lubricant promotes the growth of high-performance polymer transfer film at the friction interface, avoids direct contact between the composite material and the friction pair, and significantly improves the wear resistance of the material Sex and service life.
Smart Images

Figure BDA0005119550940000051
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer material science, and in particular to a polyurethane resin-based water-lubricated bearing composite material and a preparation method thereof. Background Art
[0002] With the rapid development of high-end technology, the deep development of marine resources has become the focus of global attention. In this context, the protection of the ecological environment is particularly important. In view of this, the use of water as a lubricating medium to replace traditional lubricating oil has become an important trend in the development of lubrication technology. At the same time, with the continuous progress and innovation of modern mechanical equipment, the market has put forward higher requirements on the performance of mechanical equipment: the pursuit of higher efficiency, lighter weight and longer service life. In this context, the concept of "sliding instead of rolling" has gradually become a new trend in the field of mechanical design, leading the industry to a more advanced direction.
[0003] Compared with traditional oil-lubricated bearings, water-lubricated bearings stand out for their environmental characteristics and cost-effectiveness. With its simple design, low cost and easy maintenance, it has been widely used in many fields such as shipbuilding, hydropower generation and military industry. However, water as a lubricating medium has certain limitations compared with lubricating oil. Water has a low viscosity, weak adsorption capacity, and limited load-bearing capacity in forming a fluid dynamic film, which makes it difficult to avoid contact between friction pairs under boundary lubrication conditions and even under dry sliding conditions. This situation can easily lead to excessive wear of water-lubricated bearing materials, which in turn poses a serious threat to the reliability and service life of the motion system. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a polyurethane resin-based water-lubricated bearing composite material with good wear resistance and long service life.
[0005] Another technical problem to be solved by the present invention is to provide a method for preparing the polyurethane resin-based water-lubricated bearing composite material.
[0006] In order to solve the above problems, the present invention discloses a polyurethane resin-based water-lubricated bearing composite material, characterized in that: the water-lubricated bearing composite material is made by mixing nano-functional fillers, solid lubricants, polyurethane matrix and polyurethane curing agent; the nano-functional fillers are any one of attapulgite powder or its derivatives; the mass ratio of the nano-functional fillers, the solid lubricants and the polyurethane matrix is 5-20:5-20:70-85; the polyurethane curing agent accounts for 20% to 35% of the mass content of the polyurethane matrix.
[0007] The polyurethane matrix is a polyether type liquid resin.
[0008] The particle size of the nano functional filler is between 50nm and 200nm.
[0009] The particle size of the solid lubricant is 5 to 10 μm.
[0010] The solid lubricant is polyethylene wax, polytetrafluoroethylene or a mixture of the two in any proportion.
[0011] The polyurethane curing agent is a diamine curing agent, which is one of MOCA, M-CDEA or DETDA.
[0012] The method for preparing the polyurethane resin-based water-lubricated bearing composite material as described above comprises the following steps:
[0013] S1 drying the nano-functional filler and the solid lubricant at 60-80°C for 6-10 hours;
[0014] S2: mixing the polyurethane matrix with the dried nano-functional filler and the solid lubricant evenly, and grinding to obtain a semi-finished product;
[0015] S3 adds polyurethane curing agent to the semi-finished product, places it in a mold after stirring and mixing, and obtains a polyurethane resin-based water-lubricated bearing composite material after demoulding and vulcanization.
[0016] The stirring and mixing condition in step S2 refers to a vacuum degree of -1.0×10 5 Pa, the rotation speed is 2000r / min, and the mixing time is 20min.
[0017] The stirring and mixing process in step S3 is performed under a vacuum degree of -1.0×10 5 Pa, rotation speed is 1800-2300r / min, and mixing time is 1-2min.
[0018] The demoulding and vulcanization conditions in step S3 refer to using a strip-type mold, thermally curing at 110° C. for 30 minutes, then removing from the mold, and transferring to a forced air drying oven at 90 to 110° C. for drying for 12 to 16 hours to obtain a strip.
[0019] Compared with the prior art, the present invention has the following advantages:
[0020] 1. The present invention is different from the traditional method of adjusting the molecular structure of polymer materials to prepare a high-performance solid transfer film that promotes the growth of the friction interface to compensate for the boundary lubrication wear of the poor water film and improve the performance of materials used in water lubrication conditions. For the first time, attapulgite is used as a functional nanofiller in a polyurethane matrix. Under water lubrication conditions, attapulgite can be effectively decomposed and transferred to the surface of the dual friction pair under the action of friction stress, while promoting the growth of a robust lubrication transfer film on the friction interface, avoiding direct contact between the composite material and the friction pair, and effectively improving the wear resistance of the composite material.
[0021] 2. The attapulgite and the added solid lubricant in the present invention have an obvious synergistic effect in improving the performance of the polyurethane matrix under water lubrication conditions, greatly improving the strength, toughness and wear resistance of the composite material, thereby effectively extending the service life.
[0022] 3. The polyurethane resin-based water-lubricated bearing composite material of the present invention can meet the requirements for reliable operation of water-lubricated bearings for pumps under multiple working conditions. DETAILED DESCRIPTION
[0023] A polyurethane resin-based water-lubricated bearing composite material is prepared by mixing a nano-functional filler, a solid lubricant, a polyurethane matrix and a polyurethane curing agent; the nano-functional filler is any one of attapulgite powder or its derivatives; the mass ratio (g) of the nano-functional filler, the solid lubricant and the polyurethane matrix is 5-20:5-20:70-85; the polyurethane curing agent accounts for 20% to 35% of the mass content of the polyurethane matrix.
[0024] The present invention introduces attapulgite nanoparticles. Since attapulgite has a catalytic effect, it can promote the carbonization transfer of polymer molecular chains, thereby promoting the growth of high-performance polymer transfer films on the friction interface. Therefore, the addition of attapulgite to the composite material can effectively improve the tensile strength, tensile modulus and toughness of the composite material.
[0025] Wherein: the polyurethane matrix is a polyether type liquid resin.
[0026] The particle size of the nano-functional filler is between 50nm and 200nm.
[0027] The particle size of the solid lubricant is 5 to 10 μm.
[0028] The solid lubricant is one of polyethylene wax and polytetrafluoroethylene or a mixture of the two in any proportion.
[0029] The polyurethane curing agent adopts a diamine curing agent, which is one of MOCA, M-CDEA or DETDA.
[0030] A method for preparing a polyurethane resin-based water-lubricated bearing composite material comprises the following steps:
[0031] S1: Place the nano-functional filler and solid lubricant into an electric blast heating oven and dry them at 60-80°C for 6-10 hours to remove water molecules adsorbed on the particle surface;
[0032] S2 stirs and mixes the polyurethane matrix with the dried nano-functional filler and solid lubricant, and the vacuum degree is -1.0×10 5 Pa, the rotation speed is 2000r / min, the mixing time is 20min, and the semi-finished product is obtained after the mixture is evenly mixed and ground;
[0033] S3 Add polyurethane curing agent to the semi-finished product and mix it in a high-speed mixer with a vacuum degree of -1.0×10 5 Pa, a rotation speed of 1800-2300 r / min, and a mixing time of 1-2 min; then placed in a mold, and after demolding and vulcanization, a polyurethane resin-based water-lubricated bearing composite material is obtained.
[0034] The demoulding and vulcanization conditions refer to using a strip-type mold, thermally curing at 110° C. for 30 minutes, then removing it from the mold, transferring it to a forced air drying oven at 90 to 110° C. for drying for 12 to 16 hours to obtain a strip.
[0035] Example 1
[0036] A method for preparing a polyurethane resin-based water-lubricated bearing composite material comprises the following steps:
[0037] S1: Place the attapulgite nanoparticles and solid lubricant into an electric blast heating oven and dry them at 80° C. for 6 hours.
[0038] S2: 85g of polyether liquid resin, 5g of dried attapulgite nanoparticles and 10g of solid lubricant were mixed and the vacuum degree was -1.0×10 5 Pa, the rotation speed is 2000r / min, the mixing time is 20min, and the semi-finished product is obtained after the mixture is evenly mixed and ground;
[0039] Wherein: the particle size of the attapulgite nanoparticles is 100 nm.
[0040] The particle size of the solid lubricant is 6 μm, and the composition of the solid lubricant is: 5 g of polyethylene wax and 5 g of polytetrafluoroethylene wax.
[0041] S3 adds MOCA to the semi-finished product, and the amount of MOCA accounts for 30% of the mass content of the polyether liquid resin. 5The mixture was stirred and mixed for 2 minutes under the conditions of 1470 Pa and a rotation speed of 2000 r / min; then placed in a mold, and after demolding and vulcanization, a polyurethane resin-based water-lubricated bearing composite material was obtained.
[0042] Example 2
[0043] A method for preparing a polyurethane resin-based water-lubricated bearing composite material:
[0044] In step S2, 80 g of polyether liquid resin, 10 g of dried attapulgite nanoparticles and 10 g of solid lubricant are stirred and mixed. The rest of the process is the same as in Example 1.
[0045] Example 3
[0046] A method for preparing a polyurethane resin-based water-lubricated bearing composite material:
[0047] In step S2, 70 g of polyether liquid resin, 20 g of dried attapulgite nanoparticles and 10 g of solid lubricant are stirred and mixed. The rest of the process is the same as in Example 1.
[0048] Comparative Example 1
[0049] The difference between this comparative example and Example 1 is that only pure polyurethane resin is used for preparation, and the preparation process is as follows:
[0050] (1) 100 g of pure polyurethane resin was placed in a high-temperature vacuum oven and preheated to 60 °C. 5 Degassing treatment was carried out at 70°C for 2 hours.
[0051] (2) MOCA is placed in a high-temperature forced air drying oven and heated to 110°C to melt it into a liquid state.
[0052] (3) Add the melted MOCA to the pure polyurethane resin, the amount of MOCA accounts for 30% of the mass content of the pure polyurethane resin, and the vacuum degree is -1.0×10 5 The mixture was rapidly stirred and mixed for 2 minutes at a speed of 2000 r / min to obtain a pure polyurethane resin material.
[0053] Comparative Example 2
[0054] The difference between this comparative example and Example 1 is that no attapulgite nanoparticles are added, and the rest are the same.
[0055] Comparative Example 3
[0056] The difference between this comparative example and Example 1 is that no solid lubricant is added, and the rest is the same.
[0057] The water-lubricated bearings made from the materials obtained in Examples 1-3 and Comparative Examples 1-3 were subjected to tribological tests and tensile tests. The friction properties of the materials were evaluated by tribological tests, and the tensile strength of the materials was evaluated by tensile tests.
[0058]
Tribology test
[0059] The tribological test was conducted using a high-speed ring-block friction and wear tester. Before the test, the materials prepared in the comparative example and the embodiment were cut into 25×10×4mm blocks. The dual friction pair was SUS304 stainless steel. The test conditions were: test load 100N, sliding speed 0.2m / s, lubricating medium was deionized water, test time 2h, and each set of friction tests was repeated at least three times. After the test, the wear scar width was measured using an optical microscope, and the corresponding wear rate was calculated using the formula. The specific calculation formula is as follows:
[0060]
[0061] Wherein, L′ is the width of the specimen (mm), R is the diameter of the dual steel ring (mm), W is the width of the wear scar (mm), F is the normal force (N), and L is the sliding distance (m).
[0062] The average friction coefficient and wear rate of the obtained materials are shown in Table 1.
[0063] Table 1 Friction coefficient and wear rate of the materials obtained in the examples and comparative examples when grinding against a stainless steel block under water lubrication conditions
[0064] Friction coefficient <![CDATA[Wear rate (mm 3 / Nm)]]> Example 1 0.09 <![CDATA[2.7×10 -5 ]]> Example 2 0.06 <![CDATA[1.3×10 -5 ]]> Example 3 0.04 <![CDATA[7.3×10 -6 ]]> Comparative Example 1 0.33 <![CDATA[1.3×10 -4 ]]> Comparative Example 2 0.17 <![CDATA[5.1×10 -5 ]]> Comparative Example 3 0.13 <![CDATA[4.5×10 -5 ]]>
[0065] As shown in Table 1, compared with pure resin (Comparative Example 1), the addition of multiple solid lubricants (Comparative Example 2) significantly reduces the friction coefficient of the material, and the wear rate is slightly reduced. The addition of nanoparticles (Comparative Example 3) slightly reduces the friction coefficient and wear rate of the material, but the effect is not very significant. The synergistic addition of solid lubricants and attapulgite nano-functional fillers further significantly reduces the friction coefficient and wear rate of the composite material (Example 3), and has the best tribological properties. Under water lubrication conditions, attapulgite and solid lubricants grow a high-strength, self-lubricating solid transfer film on the surface of the metal pair through physical and chemical effects under the action of interfacial shear force, avoiding direct contact between the friction pairs and effectively reducing the friction coefficient and wear rate of the material.
[0066]
Mechanical properties test
[0067] The tensile test was conducted using a universal testing machine. The specimen was processed into a dumbbell shape with a length of 116 mm, a thickness of 4 mm, and a gauge length of 50 mm. According to the GB / T1040-2008 standard, the tensile modulus of the material was tested at a tensile rate of 2 mm / min, and the tensile strength and elongation at break of the material were tested at a tensile rate of 50 mm / min. Each material was tested at least five times and the average value was taken. The tensile test results are shown in Table 2.
[0068] Table 2 Tensile modulus, tensile strength and elongation at break of materials obtained in Examples and Comparative Examples
[0069] Tensile modulus (MPa) Tensile strength(MPa) Elongation at break (%) Example 1 527 40.1 503 Example 2 541 41.6 512 Example 3 566 43.3 515 Comparative Example 1 352 30.7 297 Comparative Example 2 377 33.4 417 Comparative Example 3 436 38.2 302
[0070] As shown in Table 2, compared with pure resin (Comparative Example 1), the addition of solid lubricant (Comparative Example 2) slightly improves the tensile strength, modulus and elongation at break of the material, while the addition of nanoparticles (Comparative Example 3) has a more obvious effect on improving the tensile strength and modulus, but the improvement of the toughness of the material is not obvious, and the elongation at break is not improved. When the solid lubricant and the attapulgite nano-functional filler are added in synergistic manner, the strength and toughness of the composite material are greatly improved, the tensile strength is increased by about 41% compared with the pure resin, and the elongation at break is increased by about 73%. The reason is that the fibrous structure of attapulgite or its derivatives can effectively absorb the fracture energy, inhibit the growth of silver streaks inside the material, avoid stress concentration, enhance the tensile strength and tensile modulus of the polyurethane resin matrix, and show more excellent mechanical properties.
[0071] The above test results prove that the polyurethane-based water-lubricated bearing composite material of the present invention has better wear resistance and longer service life, and can meet the requirements for reliable operation of pump water-lubricated bearings under multiple working conditions.
Claims
1. A polyurethane resin-based water-lubricated bearing composite material, characterized in that: The water-lubricated bearing composite material is prepared by mixing a nano-functional filler, a solid lubricant, a polyurethane matrix and a polyurethane curing agent; the nano-functional filler is any one of attapulgite powder or its derivatives; the mass ratio of the nano-functional filler, the solid lubricant and the polyurethane matrix is 5-20: 5-20: 70-85; the polyurethane curing agent accounts for 20%-35% of the mass content of the polyurethane matrix.
2. A polyurethane resin-based water-lubricated bearing composite material as claimed in claim 1, characterized in that: The polyurethane matrix is a polyether type liquid resin.
3. The polyurethane resin-based water-lubricated bearing composite material according to claim 1, characterized in that: The particle size of the nano-functional filler is between 50 nm and 200 nm.
4. The polyurethane resin-based water-lubricated bearing composite material according to claim 1, characterized in that: The particle size of the solid lubricant is 5-10 μm.
5. A polyurethane resin-based water-lubricated bearing composite material as claimed in claim 4, characterized in that: The solid lubricant is polyethylene wax, polytetrafluoroethylene or a mixture of the two in any proportion.
6. The polyurethane resin-based water-lubricated bearing composite material according to claim 1, characterized in that: The polyurethane curing agent is a diamine curing agent, which is one of MOCA, M-CDEA or DETDA.
7. A method for preparing a polyurethane resin-based water-lubricated bearing composite material according to any one of claims 1 to 6, comprising the following steps: S1 Dry the nano-functional filler and solid lubricant at 60-80°C for 6-10 hours; S2: mixing the polyurethane matrix with the dried nano-functional filler and the solid lubricant evenly, and grinding to obtain a semi-finished product; S3 adds polyurethane curing agent to the semi-finished product, places it in a mold after stirring and mixing, and obtains a polyurethane resin-based water-lubricated bearing composite material after demoulding and vulcanization.
8. The method for preparing a polyurethane resin-based water-lubricated bearing composite material according to claim 7, characterized in that: The stirring and mixing condition in step S2 refers to a vacuum degree of -1.0×10 5 Pa, the rotation speed is 2000r / min, and the mixing time is 20min.
9. The method for preparing a polyurethane resin-based water-lubricated bearing composite material according to claim 7, characterized in that: The stirring and mixing process in step S3 is performed under a vacuum degree of -1.0×10 5 Pa, rotation speed is 1800~2300r / min, and mixing time is 1~2min.
10. The method for preparing a polyurethane resin-based water-lubricated bearing composite material according to claim 7, characterized in that: The demoulding and vulcanization conditions in step S3 refer to using a strip-type mold, thermally curing at 110° C. for 30 minutes, and then removing it from the mold and transferring it to a forced air drying oven at 90-110° C. for drying for 12-16 hours to obtain a strip.
Citation Information
Patent Citations
Modified polyformaldehyde material for flange bearing
CN101935433A
Super wear-resistant water-lubricated bearing composite material and preparation method thereof
CN106674644A
Polyurethane composite material for water-lubricated bearing and preparation method
CN108276762A
Polyformaldehyde resin material with high wear resistance and high self-lubrication performance and preparation method thereof
CN108752852A
Thermosetting polyurethane material for water-lubricated bearing and preparation method thereof
CN116515077A
Cited By
Low-friction damping polyurethane composite material as well as preparation method and application thereof
CN121227010A
High-performance polyurethane-based water lubricating material and preparation method thereof
CN121271218A